The effects of teaching and behavioral approaches on specific readiness behaviors of children with autism - Kilduff, Shanti S. (2007)
This study aimed to determine the effects of teaching and behavioral approaches on specific learning readiness behaviors of children with autism. Six children diagnosed with autism spectrum disorder were involved in the study; they were chosen on the basis of gender, chronological age, degree of autism, and degree of language-cognitive ability. They were divided into two groups, the first group was taught specific target skills by a special educator and the other group was taught by a behavioral therapist. Results showed that the children still show differences in development when specific skills are assessed, they can improve their learning behaviors, and that the special educator used more instructions while the behavior therapist used higher frequency of reinforcement. It will be beneficial for target outcomes to include other areas of development such as language and communication, gross and fine motor and self-help.
Thesis (M.A. Special Education)--University of the Philippines, Diliman.
Keywords: Autistic children -- Behavior modification; Special education -- Philippines